Whether or not heuweltjies: Context-dependent ecosystem engineering by the southern harvester termite, Microhodotermes viator. (April 2019) - McAuliffe, Joseph R.; Hoffman, M. Timm; McFadden, Leslie D.; Jack, Sam; Bell, Wesley; King, Matthew P.
Abstract: Regularly spaced earthen mounds called heuweltjies dot landscapes of the succulent Karoo of western South Africa. Colonies of the western harvester termite, Microhodotermes viator typically occupy the mounds, but there is substantial, unresolved debate regarding the role (if any) played by the colonies in mound formation. Recent studies demonstrate the role of aeolian sediment accretion in mound formation. A system dynamics model that includes a sequence of physical and biological state transitions illustrates processes that culminate in the localized deposition of aeolian sediments in a patch occupied by a colony of M. viator. The process starts with the successful establishment of a termite colony. As the colony develops, the termites accumulate soil nutrients, creating a fertile island, which fosters localized development of denser vegetation. The vegetation patch functions as a sediment trap, accumulating greater amounts of aeolian sediments than in the surrounding, sparser vegetation. Positive feedback loops contribute to continuity of patch occupancy by termites and persistence of processes responsible for mound formation and maintenance. System behavior is dependent on exogenous environmental variables, including climate and sediment supply. This context-dependent behavior explains geographical variation in mound size and the occurrence of other physical manifestations of colonies. Highlights: System dynamics model illustrates transitions involved in formation of heuweltjies. Establishment of termite colony generates a nutrient-enriched fertile island. Plant responses to soil changes creates a dense vegetation patch. Vegetation patch acts as aeolian sediment trap leading to mound formation. System behavior is highly dependent on physical environmental variables.